2000
DOI: 10.4049/jimmunol.164.6.3345
|View full text |Cite
|
Sign up to set email alerts
|

The Coupling of 5-Oxo-Eicosanoid Receptors to Heterotrimeric G Proteins

Abstract: 5-Oxo-eicosatetraenoic acid (5-oxoETE) stimulated human neutrophil (PMN) and eosinophil chemotaxis, PMN hexose uptake, and PMN membrane GTP/GDP exchange. Pertussis toxin (PT), a blocker of heterotrimeric G proteins (GP), completely inhibited these responses, but proved far less effective on the same responses when elicited by leukotriene B4, C5a, FMLP, platelet-activating factor, IL-8, or RANTES chemotactic factors. 5-OxoETE also specifically bound to the membrane preparations that conducted GTP/GDP exchange. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…However, in primary human eosinophils, we observed that neither PGD 2 nor indomethacin responses were inhibited by PTX under conditions where this toxin completely inhibited eotaxin/CCL11-induced eosinophil shape change. These data suggest that CRTH2 in eosinophils may perhaps be coupled, at least in part, to the PTX-resistant G protein G␣ q/11 which is also involved in eosinophil chemotactic responses to other ligands, although interpretation of PTX-dependence in investigation of agonist-mediated responses must be carried out with caution (50). An alternative hypothesis, that the actions of both indomethacin and PGD 2 on eosinophils are mediated predominantly via the PTX-resistant DP receptor rather than CRTH2, is unlikely, given the published specificity of indomethacin and the previous data on the selective roles of CRTH2 in mediating eosinophil PGD 2 responses (26 -28, 36).…”
Section: Discussionmentioning
confidence: 97%
“…However, in primary human eosinophils, we observed that neither PGD 2 nor indomethacin responses were inhibited by PTX under conditions where this toxin completely inhibited eotaxin/CCL11-induced eosinophil shape change. These data suggest that CRTH2 in eosinophils may perhaps be coupled, at least in part, to the PTX-resistant G protein G␣ q/11 which is also involved in eosinophil chemotactic responses to other ligands, although interpretation of PTX-dependence in investigation of agonist-mediated responses must be carried out with caution (50). An alternative hypothesis, that the actions of both indomethacin and PGD 2 on eosinophils are mediated predominantly via the PTX-resistant DP receptor rather than CRTH2, is unlikely, given the published specificity of indomethacin and the previous data on the selective roles of CRTH2 in mediating eosinophil PGD 2 responses (26 -28, 36).…”
Section: Discussionmentioning
confidence: 97%
“…This eicosanoid is known as a potent chemotactic factor of eosinophils and neutrophils (37)(38)(39)(40). O'Flaherty et al (41,42), and O'Flaherty and Rossi (43) had revealed that the chemotactic activity would be mediated through a pertussis toxin-sensitive GPCR. As a separate line of interesting studies on 5-oxo-ETE and the derivatives, Ghosh and Myers (44,45) had identified 5-oxo-ETE and 5-HETE as mitogenic as well as anti-apoptotic factors in prostate cancer cells.…”
Section: Fig 5 Effect Of 5-oxo-ete On Forskolin-stimulated Camp Promentioning
confidence: 99%
“…The biological actions of this compound are mediated by the highly selective OXE receptor (10,11), which is a member of the G protein-coupled receptor family (12)(13)(14). The objective of the current study was to determine whether sebaleic acid is a substrate for the 5-LO pathway and whether it can be converted to biologically active proinflammatory products that could potentially be involved in attracting granulocytes to the skin.…”
mentioning
confidence: 99%